Verbalization of Female Artistic Images in “A Thousand Splendid Suns” by Khaled Hosseini: Gender Aspect - Muntian, Antonina O.; Shpak, Iryna V. (Національний університет “Острозька академія”, Острог, 2020)
EN: Annotation: The purpose of this study is an attempt to examine women's artistic images and their verbalization in Khaled Hosseini's novel “A Thousand Splendid Suns”. In this study, the authors try to analyze the manifestations of the feminine discourse of the two main female characters in the novel “A Thousand Splendid Suns” in sociocultural and linguostylistic aspects. In the recent years women’s studies are becoming more and more significant; female discourses are being analyzed form different scientific points of view. Considering the relevant scientific works of eminent scientists, the authors of this article conclude that artistic images play an extremely important role in the implementation of current topics and ideas of any literary work: artistic images have the ability to produce new ideas and communicate these ideas to readers who in their turn could interpret them according to the cultural background, which ensures the formation of the linguistic and cultural concepts. Khaled Hosseini’s female characters’ discourse in his novel “A Thousand Splendid Suns” is multilayered: on the one hand, it is actualization of the personal fight for basic human rights within family hierarchy (cultural aspect) and on the other hand, it is the fight for civil rights from the point of view of social context.

UK: Анотація: Метою даного дослідження є спроба дослідити жіночі художні образи та їхню вербалізацію в романі Халеда Хоссейні «Тисяча сяючих сонць». В даному дослідженні автори роблять спробу проаналізувати маніфістації фемінінного дискурсу двох головних жіночих персонажів роману «Тисяча сяючих сонць» у соціокультурному та лінгвостилістичному аспектах. Останніми роками вивчення жіночих дискурсів набирає значущості в різних сферах науки, а також зростає більшість досліджень і цій галузі. Розглянувши відповідні наукові праці видатних вчених, автори даної статті доходять висновку, що художні образи відіграють надзвичайно важливу роль у реалізації актуальних тем і ідей будь-якого літературного твору: художні образи мають здатність продукувати нові ідеї та передавати ці ідеї читацькій аудиторії, щоб читачі, у свою чергу, могли інтерпретувати їх відповідно культурному бекграунду, що забезпечую формування лінгвокультурного концепту. Дискурс жіночих персонажів в романі Халеда Хоссейні «Тисяча сяючих сонць» варто розглядати на кількох рівнях: з одного боку, це актуалізація особистої боротьби за базові права в родині (культурологічний аспект), а з іншого боку – це боротьба за громадянські права та свободи з точки зору соціального контексту.
Вербалізація жіночих художніх образів в романі Халеда Хоссейні «Тисяча сяючих сонць»
A. Muntian: ORCID 0000-0001-8375-4067, I. Shpak: ORCID 0000-0002-4305-4987
Keywords: novel; literary work; artistic image; literary character; linguacultural concept; роман; літературний твір; художній образ; літературний персонаж; лінгвокультурний концепт; КІМ